Utilisation de la mielga (Medicago sativa L.) dans la constitution des prairies permanentes - Ben Chaâbane A.A.; Delgado Enguita I. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
The rhizomatous alfalfas are appreciated for their tolerance to drought and rambling which makes them very interesting for grazing in semi-arid regions. A 'mielga' population from Spain, characterised by a rhizomaous habit, was compared in this study with the hay-type cultivar Aragón under a 15 days-frequence defoliation regime. Top-growth protein content and crown diameter were analysed. The mielga population showed an appreciable and stable protein content across the cuts, although lower on average than that of Aragón. On the contrary crown diameter was larger in the mielga than in the hay-type cultivar.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)